2011
DOI: 10.1111/j.1600-0722.2011.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Short mandible, maxilla and cranial base are common in patients with neurofibromatosis 1

Abstract: Neurofibromatosis type 1 (NF1) is an autosomal-dominant neuro-cutaneous-skeletal syndrome. Neurofibromatosis type 1 is one of the Rasopathies, and at the cellular level NF1 results in a hyperactive Ras pathway. In the current investigation, our aim was to study lateral skull X-rays (cephalograms) to assess NF1-related craniofacial morphology. A total of 85 Finnish patients with NF1, including four patients with plexiform neurofibroma of the 5th cranial nerve, and their age- and gender-matched controls, were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
3
22
2
Order By: Relevance
“…In this dataset of American whites with NF1, we confirmed (in a modestly larger sample) many of the findings found by Heerva et al . [8] in an NF1 Finnish cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this dataset of American whites with NF1, we confirmed (in a modestly larger sample) many of the findings found by Heerva et al . [8] in an NF1 Finnish cohort.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also hypothesized to develop due to a primary bone cell-autonomous defect [5]. An analysis of NF1 cephalometry was first published by Heervä et al in 2011, who found that individuals with NF1 typically had a shorter mandible, maxilla and cranial base compared to controls [8]. The sphenoid bone is a key component of the anterior cranial base.…”
Section: Introductionmentioning
confidence: 99%
“…On prenatal ultrasonography, maxillary hypoplasia can appear as an incidental finding or can be part of a structural malformation, a genetic syndrome or a chromosomal anomaly . When searching the literature and the Online Mendelian Inheritance in Men database, the term maxillary hypoplasia results in syndrome citations, such as Marfan syndrome and genetic disorders such as Neurofibromatosis type 1 . Additionally, maxillary hypoplasia has been described as a consistent clinical finding in fetuses and newborns with Down syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Visualization of the fetal maxillary bone is possible from early weeks of gestation onwards and important information can be drawn from the examination of abnormal fetal maxillary development . During routine prenatal evaluation, maxillary hypoplasia may occur as an isolated finding, but may also lead to the detection of structural abnormalities, genetic disorders or syndromes . Thus, it is clinically relevant to have normative curves of maxillary growth pattern of normal fetuses to allow the diagnosis of pathologies as early during pregnancy as possible .…”
Section: Introductionmentioning
confidence: 99%
“…NF1 is characterized by the predisposition to benign and malignant tumors of the peripheral and central nervous system. NF1 patients may also exhibit noncancerous symptoms such as the presence of café-au-lait macules, axial freckling, learning disabilities, and skeletal dysplasia [2,3]. Clinically, NF1 patients exhibit skeletal congenital or developmental abnormalities, resulting in alterations in bone shape or size.…”
Section: Introductionmentioning
confidence: 99%